2017
DOI: 10.5811/cpcem.2016.11.33052
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Ectopic Pregnancy in a 23 Year Old with Uterus Didelphys

Abstract: Ectopic pregnancy remains an important diagnosis for the emergency physician to recognize, accounting for up to 2% of all pregnancies and associated with significant morbidity and mortality. Ectopic pregnancies can implant in various sites outside of the uterus, one of the rarest of which is in the cervix. Cervical ectopics account for less than 1% of ectopic pregnancies, but are associated with higher rates of significant bleeding than others.1–2 Uterine anomalies are a predisposing factor for ectopic pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Patrick et al managed a patient diagnosed with uterine diadelphous with a cervical pregnancy bHcg level of 6045 mIU / ml with vaginal bleeding at an early gestational week by administering methotrexate treatment. In our case, curettage was applied because methotrexate treatment was not appropriate due to the advanced gestational week (21). Another case study was reported by Chandrasekhar et al, two cases of UD, one cervical and the other cornual.…”
Section: Fig 3 the Total Right Hemihysterectomymentioning
confidence: 73%
See 1 more Smart Citation
“…Patrick et al managed a patient diagnosed with uterine diadelphous with a cervical pregnancy bHcg level of 6045 mIU / ml with vaginal bleeding at an early gestational week by administering methotrexate treatment. In our case, curettage was applied because methotrexate treatment was not appropriate due to the advanced gestational week (21). Another case study was reported by Chandrasekhar et al, two cases of UD, one cervical and the other cornual.…”
Section: Fig 3 the Total Right Hemihysterectomymentioning
confidence: 73%
“…In our case, uterine diadelphous and cervical ectopic pregnancy were observed together as a rare situation. Few cases have been reported on this subject in the literature (21)(22)(23). Patrick et al managed a patient diagnosed with uterine diadelphous with a cervical pregnancy bHcg level of 6045 mIU / ml with vaginal bleeding at an early gestational week by administering methotrexate treatment.…”
Section: Fig 3 the Total Right Hemihysterectomymentioning
confidence: 99%
“…The septate uterus is most common at 35% followed by bicornuate at 25%, then arcuate at 20%, then unicornuate at 9.6%, and complete agenesis at 3%. 4 Heinonen PK, evaluated the long-term clinical consequences, and reproductive performances of 49 women with uterus Didelphys that were followed up to 6.3 years. 1 According to the study the recurrent miscarriage rate is 21%, ectopic pregnancy rate is 2%, fetal survival rate is 75%, prematurity is 24%, IUGR 11%, caesarian rate is 84%.…”
Section: Discussionmentioning
confidence: 99%
“…Reported data regarding the clinical outcomes and implications of women with uterus didelphys are limited. Most available studies are case reports [13][14][15] or small retrospective series that lack case controls for potential confounding factors 11,12,16 , which makes it difficult to determine the relationship between uterus didelphys anomalies and adverse pregnancy outcome. Moreover, there is wide deviation in reported outcomes; for example, the reported miscarriage rate varies between 21.0% and 69.0%, and the preterm birth rate has been estimated to be 16.7% to 53.3% 11,[16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%